The Role of Technology Adoption in Scaling Startupreneur Business Models in the Digital Economy - Delhi, Ariana; Sijabat, Apriani (Pandawan Sejahtera Indonesia, 2024)
Technology adoption plays a vital role in the digital business landscape, enabling startupreneurs to scale their businesses efficiently. In the era of the digital economy, adopting the right technologies can drive growth and enhance competitiveness. This study aims to understand how technology adoption contributes to the scaling of startupreneur business models. Using a mixed-methods approach, data was collected through quantitative surveys and in-depth interviews with 200 startupreneurs. The results indicate that cloud computing, e-commerce platforms, and mobile apps are the most impactful technologies, with cloud computing driving 30% business growth and 20% cost reduction. These findings highlight the importance of strategic technology adoption for startupreneurs seeking to expand their operations. The study offers practical insights into how startupreneurs can leverage digital tools for sustainable growth, and future research should explore the long-term impacts of emerging technologies like AI and blockchain.